2021
DOI: 10.1371/journal.pone.0247861
|View full text |Cite
|
Sign up to set email alerts
|

Urinary cytokines in women with refractory detrusor overactivity: A longitudinal study of rotating antibiotic versus placebo treatment

Abstract: Over 50% of women with detrusor overactivity (DO), who do not respond to therapy have been shown to have bacteriuria, which may stimulate the release of inflammatory cytokines than can enhance nerve signalling, leading to symptoms of urgency. This study made use of a consecutive series of urine samples collected from women with refractory DO, who participated in a clinical trial of rotating antibiotic therapy. The aim was to determine the effect of bacteriuria and antibiotic treatment on the levels of urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Using samples collected as part of the phase IIb trial described above, we were able to investigate the mechanisms behind the improvement in outcomes in the OAB patients. Our follow-up analysis of the trial cohort revealed that cytokines associated with activation of the innate immune system are reduced by antibiotic therapy in women with OAB ( Chen et al, 2021b ). In particular, antibiotic treatment was associated with significant reductions of pro-inflammatory cytokines IL-1α, IL-1Ra, IL-6, IL-8, and CXCL-10 and the anti-inflammatory cytokine IL-10, which are all cytokines typically present in UTIs ( Sundac et al, 2016 ).…”
Section: Evidence and Implications For Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Using samples collected as part of the phase IIb trial described above, we were able to investigate the mechanisms behind the improvement in outcomes in the OAB patients. Our follow-up analysis of the trial cohort revealed that cytokines associated with activation of the innate immune system are reduced by antibiotic therapy in women with OAB ( Chen et al, 2021b ). In particular, antibiotic treatment was associated with significant reductions of pro-inflammatory cytokines IL-1α, IL-1Ra, IL-6, IL-8, and CXCL-10 and the anti-inflammatory cytokine IL-10, which are all cytokines typically present in UTIs ( Sundac et al, 2016 ).…”
Section: Evidence and Implications For Clinical Practicementioning
confidence: 99%
“…This variability is further compounded by the relatively small number of patients included in these studies. Despite these issues, there is a growing consistency in the evidence for elevations in pro-inflammatory cytokines TNF-α ( Tyagi et al, 2010 ; Ma et al, 2016 ; Chen et al, 2019 ), MCP-1 ( Tyagi et al, 2010 ; Chen et al, 2019 ; Farhan et al, 2019 ; Ghoniem et al, 2020 ) and MIP-1 ( Tyagi et al, 2010 ; Ma et al, 2016 ) as well as reductions in anti-inflammatory cytokines IL-10, IL-1 receptor antagonist, and IL-4 ( Ma et al, 2016 ; Tyagi et al, 2016 ; Pillalamarri et al, 2018 ) in OAB patients. A shift in the balance of these cytokines to a more pro-inflammatory state, and a lack of anti-inflammatory cytokines in women with OAB, may allow an inflammatory response to proliferate, thus contributing to the pathogenesis of the disease ( Pillalamarri et al, 2018 ).…”
Section: Infection Induced Inflammation In Patients With Overactive B...mentioning
confidence: 99%